ANALISA BAURAN PEMASARAN TERHADAP PENJUALAN PADA WARUNG LODHO AYAM KAMPUNG BAPAK’E - Sisilia, Firdya (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated because the efforts to implement the marketing mix have not been maximally achieved by Warung Lodho Ayam Kampung Bapak'e. In order for warungs to improve their marketing mix activities, they must pay attention to product quality, price, place, promotion. The purpose of this study was to find out that the sales turnover of Warung Lodho Ayam Kampung Bapak'e continued to increase despite a lot of competition. This research is included in the category of descriptive research with the use of a qualitative approach. Qualitative approach is used because all phenomena of research results are presented in narrative form and interpreted as necessary. Therefore, this field research has the aim of describing, revealing, explaining the marketing mix implemented by the stall. The results of this study are (1) selling quality products (2) setting the selling price according to the quality and taste offered (3) choosing a strategic location by providing comfortable dining and facilities (4) promotions carried out online and offline.